A cross-sectional, multi-centric, epidemiology study to determine the prevalence of insomnia and related sleep habits in Indian hypertensive patients - Karnik, Rajiv; Peethambaran, Karthik; Adsule, Samir (International Journal of Research in Medical Sciences, 2017)
Background: Hypertension is a leading risk factor affecting mortality and disability-adjusted life years worldwide. The objective of the study was to determine the prevalence of insomnia, co-morbid medical conditions, lifestyle attributes, related sleep habits and sleep quality among Indian hypertensive patients. Methods: Adults (≥18 years) with newly diagnosed or known history of hypertension, willing to participate were enrolled in this cross-sectional, epidemiological study. Several variables including lifestyle attributes, sleep habits, quality, medications, demographics, medical/surgical history and other details pertaining to hypertension were analyzed. Insomnia was assessed by Athens Insomnia Scale (AIS) in patients not identified in the past one month. Results: All the 657 enrolled patients completed the study (mean age: 55.4±11.61 years; men: 53.7%; women: 46.3%). Prevalence of insomnia among hypertensive population was approximately 47.2% (n=310; 95% CI: 43.4, 51.0). Number of patients newly diagnosed with insomnia by AIS scale was higher compared with patients already diagnosed with insomnia (34.9% [95% CI: 31.2, 38.5] vs. 12.3% [95% CI: 9.81, 14.8]). Common medical conditions associated with hypertension were diabetes mellitus (61.1%) and dyslipidemia (28.3%). More than half of the hypertensive patients with insomnia had sleep-related problems once or twice a week. Further, the daytime impact of insufficient sleep on wellbeing and functioning was markedly decreased in insomniac patients. Conclusions: Prevalence of insomnia among patients suffering from hypertension was higher than that reported in general Indian population in various studies. Present study shows that about 75% insomniac cases were undiagnosed, indicating that insomnia diagnosis may have been missed in a large proportion of hypertensive patients.